Fish vertebra from Miocene beds at Govce, Slovenia - Mikuž, Vasja; Bartol, Miloš; Ulaga, Špela (Geologija, 2014)
The article discusses a vertebra and a small shark tooth found in the Miocene Govce sandstone near Govce west of Laško in central Slovenia. The vertebra belongs to a shark of the superorder Galeomorphii but we could not determine it with greater precision. The small tooth was assigned to Carcharias cf. taurus Rafmesque, 1810. The nannofossils in the sample are scarce and did not allow dating at biozone precision.